Domains of practice and Advanced Practice Nursing in Australia. (21st May 2013) - Roche, Michael; Duffield, Christine; Wise, Sarah; Baldwin, Richard; Fry, Margaret; Solman, Annette
Abstract A key component of workforce reform is the international growth in Advanced Practice Nursing (APN) roles. This study evaluated one APN role in Australia, the Clinical Nurse Consultant (CNC). All 56 CNCs employed in a tertiary hospital in New South Wales took part in the study. Demographic and work activity data were collected by an online questionnaire. Face‐to‐face interviews included the administration of a 50‐point tool to score the level of practice of each CNC against five domains. The domains of practice did not appear to have played a central role in the design of these CNC roles despite being defined in the industrial legislation and linked to a pay structure. There was widespread variability in the level of practice both within and between the CNC grades as well as significant differences in job content. Few CNCs managed to achieve a moderate level of practice across all five domains. The findings suggest that the distinctive features of the CNC roles as articulated in the domains of practice are often not realized in practice.